Peran Burn Out Dan Role Stress Dalam Memediasi Beban Kerja Terhadap Kepuasan Kerja Studi Pada Tenaga Keperawatan Rumah Sakit Di Cirebon - Nunung Nurmalasari; Nur Adila Sari; Nillam Lay Nur; Edy Hartono (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to examine the effect of Workload on Job Satisfaction with Burnout and Role Stress as mediating variables. This study uses quantitative methods that aim to analyze whether there is a relationship between the variables studied and to confirm the theory with PLS-SEM (Partial Least Square - Structural Equation Modeling) analysis. The sample in this study was 192 respondents of nursing staff in 3 hospitals in Cirebon, West Java, which were taken by random sampling. The results showed that Workload has a significant positive effect on burnout with a P-value (0.00 < 0.05) and a T-Table of (16.725 > 1.96), Workload has a significant positive effect on job satisfaction with a P-value (0.00 < 0.05) and a T-Table of (11.277 > 1.96), Workload has a significant positive effect on role stress with a P-value (0.00 < 0.05) and a T-Table of (9.588 > 1.96). Furthermore, the results of this study found that Role Stress is able to mediate the effect of Workload on Job Satisfaction with a T-Table value of (6.407 > 1.96) and a P-value of (0.000 < 0.05), Burnout is able to mediate the effect of Workload on Job Satisfaction with a T-Table value of (3.549 > 1.96) and a P-value of (0.000 < 0.05).